Understanding AI Literacy Among College Students: Voices from a Historically Black College and University - Threadgill, Benita; Paudel, Surakshya; Bista , Krishnna; Gaulee, Uttam; Prime , Glenda; Momoh, Victory; Anderson, Patricia Crispin; Gole , Ricky; Sharma , Sujata; Mandal , Urasha; Rajput , Manisha; Garbuja, Smriti; et al. (Journal of Interdisciplinary Studies in Education, 2026)
This qualitative case study explores how students at a Historically Black College and University (HBCU) perceive, use, and critically reflect on artificial intelligence (AI) within academic and personal contexts. Guided by a four-dimensional framework: conceptual understanding, application skills, ethical awareness, and critical reflection, semi-structured interviews with 28 undergraduate and graduate students from one mid-Atlantic public research university revealed both opportunities and challenges. Students viewed AI as a supportive “assistant” that enhances efficiency in writing, communication, and learning, but demonstrated limited technical knowledge and occasional uncritical reliance on outputs. Ethical concerns, particularly regarding plagiarism, bias, and data privacy, were prevalent, alongside strong calls for institutional guidance. Findings highlight the need for equity-driven, curriculum-integrated AI literacy initiatives to ensure responsible, critical, and inclusive engagement with emerging technologies.